Exploring English Language Teachers’ Professional Agency: A Phenomenological Study - Khanal, Sharada; Neupane, Bharat Prasad; Bhatt, Surendra Prasad; Dewan, Motikala Subba (Journal of NELTA, 2025)
The study explores English language teachers’ perceived and enacted experiences of their professional agency in the educational environment in Nepal. Employing phenomenology as a research method and subscribing to the ecological model of teacher  agency, this article strives to comprehend the lived experiences of four purposively selected participants from two colleges in Chitwan through in-depth interviews. The findings reveal the evolving nature of teaching, marked by the increasing use of technology in the educational environment. English language teachers shift to interactive approaches, such as discussion, group work, and the use of videos. During times of unprecedented challenges, teachers adapted through constant learning and making real-world decisions. It also portrays teachers as role models and agents of change, who have control over their own teaching and learning activities by making self-directed decisions about lesson planning, guiding learners, and ensuring timely course completion. The article implies that institutions can create an environment that empowers teachers, fosters professional growth, and enhances language learning outcomes. Concluding, empowering teacher agency can lead to more adaptive and innovative teaching and learning practices.